Injuries among students combining academic studies and elite sports - Flatholm, E.; Tengman, E.; Tervo, T. (Frontiers in Sports and Active Living, 2025)
Objective: The purposes of the study were to examine injury incidence among students engaged in elite sports during their first year of study, and to explore factors associated with injury in this population.